PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO DISERTAI SPEED TEST TERHADAP PPEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN PITALAH - Indra Glora, Mega; Rahmi, Rahmi; ZA, Nilawasti (Pendidikan Matematika, 2014)
ABSTRACTÂ This research is motivated by the understanding of mathematical concepts MTsN Pitalah eighth grade students is still low. This is because students are not trained to work with her in learning and they do not understand about the concept that should be used in work on the problems set by the teacher. This study aims to determine whether studentsâ understanding of mathematical concepts by applying active learning strategies The Power Of Two types accompanied Speed Test better than the studentsâ understanding of mathematical concepts by applying conventional learning strategies The Power Of Two accompanied Speed Test to eight grade students learning mathematics MTsN Pitalah Kab. Tanah Datar. This type of research is experimental. Random sampling technique to the subject. The instrument used is the Speed Test and final test students understanding of mathematical concepts. Form of the test used is the reliability 0,821 essay. The results obtained from testing the hypothesis t=Â  2,5 is greter than t table = 0,05 then the hypothesis is accepted. It can be concluded that the studentsâ understanding of mathematical concepts by applying active learning strategies The Power Of Two types accompanied Speed Test better than student understanding of mathematical concepts by applying conventional learning eighth grade students MTsN Pitalah Kab. Tanah Datar.